Developing a Mobile Application as a Learning Medium on Maternal Emergencies Related to Postpartum Hemorrhage: 10.55131/jphd/2022/200104 - Vike Pebri Giena; Ruri Maiseptya Sari; Fatima Nuraini Sasmita; Ida Rahmawati (Journal of Public Health and Development, 2022)
Maternal mortality (MM) remains a problem in the world as 380 mothers die from complications related to pregnancy and childbirth worldwide. Postpartum hemorrhage is the world’s leading cause of maternal mortality. In Indonesia, there were 8,600 maternal mortality cases in 2017, while the target to be achieved by 2025 is 74 per 100,000 live births. The aim of this study was to develop a mobile application as a learning medium on maternal emergencies. A research and development (R&D) study was conducted on 56 midwifery students, who were selected by total sampling. The KGD (KeGawatDaruratan) Maternal application was developed by using the ADDIE (analyze, design, develop, implement, evaluate) instruction model and was validated by two experts, namely, midwifery and media experts. The KGD Maternal application was assessed by midwifery students using structured questionnaires named the Technology Acceptance Model (TAM) questionnaires, which covered perceived ease of use (PEOU) and perceived usefulness (PU). The results of this study revealed that the KGD Maternal application was considered valid by the material expert and very valid by the media expert. As many as 69.6% of the midwifery students rated the KGD Maternal application as useful in the learning process on maternal and neonatal emergencies, and 73.2% rated it as easy to use. This study also revealed that the KGD Maternal application could provide greater opportunities for midwifery students to access, and facilitate and enable them to understand, materials about maternal emergencies. Based on the findings in this study, institutions of midwifery and nursing education should design and develop learning media that can provide a more optimal learning process. Furthermore, a higher extent of mobile application development is needed to provide better learning media. Increased knowledge and competency will clearly result in decreased maternal mortality.